Virtual Reality applied to Exposure Therapy for Obsessive Compulsive – Disorder - Sofia Petito Alexandre; Catarina Chasqueira; Shihan Wang; Catarina Furtunato (User Experience & Urban Creativity)
Obsessive-compulsive disorder (OCD) is a mental illness that causes repeated unwanted thoughts or sensations (obsessions) or the urge to do something over and over again (compulsions). OCD has various subtypes, including the fear of contamination in which individuals fear bacteria, germs, disease, or bodily secretions, and engage in clinically significant cleaning and avoidance rituals. In recent years, Virtual Reality (VR) has shown the potential to cure people suffering from anxiety disorders and OCD in exposure and response prevention therapy. The objective of this study is to create an application with VR for doctors which helps them during treatments nameded e-toc. So in this case, VR is one alternative to cure patients without using medication. This application simulates uncomfortable situations for people to overcome their obsession and compulsive behaviour. This project is developed in an application divided into two parts: one part designed to be used by the therapist - creation, planning, and implementation of therapy and another to be used by the patient - use of virtual reality mechanisms, such as glasses, heart rate meter, gloves that allow the capture of movements. Although the application was created and developed with the patient in mind, with the development of the project, there was a need to support the therapist, mainly due to the planning and monitoring of the treatment. During treatment, when the patient is ready the presentation of the videos begins. While using the Virtual Reality mechanisms - glasses, headphones, watches that measure the heartbeat, and the gloves or rings that capture the patient's movements, the therapist has access to all the information.